2003
DOI: 10.1002/da.10086
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes in people told that they have panic attacks

Abstract: We sought to identify predictors of being told the diagnosis of panic by health care providers and to assess whether being told affected outcomes. We collected data about care-seeking behavior, panic and family characteristics, psychiatric comorbidity, and illness behaviors. Outcomes included psychiatric symptomatology, disability, substance use, and control. Presentation to an emergency department and the number of mental health sites used predicted being told. Patient predictors centered on symptom severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The community-based Panic Attack Care-Seeking Threshold (PACT) Study [147,150,151,152,153,154,155,156] showed how some IAS are specifically associated with various clinical features of panic disorder. High scores on the treatment experience, effects of symptoms and worry about illness scales were respectively independent predictors of seeking medical care for panic attacks [150, 153, 155], panic-related work disability [152] and quality of life [152].…”
Section: Resultsmentioning
confidence: 99%
“…The community-based Panic Attack Care-Seeking Threshold (PACT) Study [147,150,151,152,153,154,155,156] showed how some IAS are specifically associated with various clinical features of panic disorder. High scores on the treatment experience, effects of symptoms and worry about illness scales were respectively independent predictors of seeking medical care for panic attacks [150, 153, 155], panic-related work disability [152] and quality of life [152].…”
Section: Resultsmentioning
confidence: 99%
“…Possible strategies for earlier identification include educating physicians in other specialties about PD symptoms, which may help medical professionals understand the influence of health-seeking behavior on PD patients' QOL. Providing patient handouts about PD for use in emergency departments and family practice offices may help educate many patients with PD who are first informed of their disorder in these settings [53]. Additionally, employing a mass media campaign on PD symptoms and appropriate therapy may help to guide patients with PD symptoms to actively seek early psychiatric care to reduce the impact of PD on their physical and psychosocial health status, and ultimately on QOL.…”
Section: Implications For Clinical Practice and Further Researchmentioning
confidence: 97%
“…Usually the factors identified by these methods related to severity of illness, comorbidity and presence of personality disorders and noncompliance with the treatment. 39,40 Studies analyzing usual care delivery in primary care produced some insight on treatment resistance in 'care as usual'. 41 The studies indicated that inadequate recognition, inadequate training, incorrect use of antidepressants and lack of understanding and the use of CBT are among the main reasons for patient's non-response.…”
Section: Predictors Of Nonresponse In Clinical Literaturementioning
confidence: 99%